TECHNOLOGICAL TRANSPORT ROUTE OPTIMIZATION USING ARCVIEW GIS AND ARCVIEW NETWORK ANALYST SOFTWARE - S. A. Laptionok (Наука и техника)
The paper reveals a possibility to apply ArcView GIS и ArcView Network Analyst software for an interactive spatial modeling and optimization of routes. The spatial  models of technological municipal transport routes are presented are presented in the paper.